Immunization of pigs with replication-incompetent adenovirus-vectored African swine fever virus multi-antigens induced humoral immune responses but no protection following contact challenge - Zajac, Michelle D.; Trujillo, Jessie D.; Yao, Jianxiu; Kumar, Rakshith; Sangewar, Neha; Lokhandwala, Shehnaz; Sang, Huldah; Mallen, Kylynn; McCall, Jayden; Burton, Leeanna; Kumar, Deepak; Heitmann, Emily; et al. (Frontiers in Veterinary Science, 2023)
African Swine Fever Virus (ASFV) is a pathogen of great economic importance given that it continues to threaten the pork industry worldwide, but there is no safe vaccine or treatment available. Development of a vaccine is feasible since immunization of pigs with some live attenuated ASFV vaccine candidates can confer protection, but safety concerns and virus scalability are challenges that need to be addressed. Identification of protective ASFV antigens is needed to inform the development of efficacious subunit vaccines. In this study, replication-incompetent adenovirus-vectored multicistronic ASFV antigen expression constructs that covered close to 100% of the ASFV proteome, were generated and validated using ASFV convalescent serum. Immunization of pigs with a cocktail of the expression constructs, designated Ad5-ASFV, alone or formulated with either Montanide ISA-201™ (ASFV-ISA-201) or BioMize® adjuvant (ASFV-BioMize), primed strong B cell responses as judged by anti-pp62-specific IgG responses. Notably, the Ad5-ASFV and the Ad5-ASFV ISA-201, but not the Ad5-ASFV BioMize®, immunogens primed significantly (p<0.0001) higher anti-pp62-specific IgG responses compared to Ad5-Luciferase formulated with Montanide ISA-201™ adjuvant (Luc-ISA-201). The anti-pp62-specific IgG responses underwent significant (p<0.0001) recall in all the vaccinees after boosting and the induced antibodies strongly recognized ASFV (Georgia 2007/1)-infected primary swine cells. However, following challenge by contact spreaders, only one pig that had been immunized with the Ad5-ASFV cocktail survived. The survivor had no typical clinical symptoms, but it had viral loads and lesions consistent with chronic ASF. Besides the limited sample size used, the outcome suggests that in vivo antigen expression, but not the antigen content, might be the limitation of this immunization approach since the replication-incompetent adenovirus does not amplify in vivo to effectively prime and expand protective immunity or directly mimic the gene transcription mechanisms of attenuated ASFV. Addressing the in vivo antigen delivery limitations will likely yield promising outcomes.